The feeding preferences of Spodoptera frugiperda (J. E. SMITH) (Lepidoptera: Noctuidae) on cotton plant varieties - Zeneide Ribeiro Campos (Acta Scientiarum. Agronomy, 2012)
This work evaluated the attractiveness and th e non-preference for feeding of newly hatched fall armyworm larvae on the cotton plant parts and different varieties used in the study. The trials were performed at 27 ± 1ºC, a 70% ± 10% relative humidit y and a 14h photoperiod. Leaves, bracts, squares and carpel walls of the BRS Itamarat i-90 variety and leaves of Fiberm ax-966, Fibermax-977, DeltaOpal, DeltaPenta, BRS Acala-90, Coodetec-408, Coodetec -409, Coodetec-410, BRS- Cedro, BRS-Ipê, BRS- Aroeira, IPR-96, IPR-120, BRS-Araçá, IAC-24 and BRS Itamarati-90 varietie s were used in attractiveness, multiple-choice and confinement (no-choice) non-prefer ence feeding trials. Twenty larvae were released per petri dish test (arena system) with 10 repetitions. Attractive ness trials were evaluated by counting feeding caterpillars over 60 min. and by measuring non- preference at 24h. Leaves were the most attractive item and were preferred for feeding. In the mult iple-choice arena trials, Coodetec-410 was the most attractive variety, and BRS Acala- 90, Fibermax-966 and DeltaPenta we re the least attractive to fall armyworm larvae. In the non-preferen ce trial, BRS-Araça was the variet y favored for feeding. BRS-Cedro, BRS Itamarati-90, DeltaPenta, Coodetec-408 and BRS-Ar oeira were the least-favo red varieties. In the 60 min. attractiveness trials, 46 min. proved to be the most suitable time for evaluating the attractiveness of cotton plants to newly hatched fall armyworm larvae.